Advances in neuropathic pain management: A review of real-world studies - Swati S. Dash; Nikhil K. Khatri; Saraswathi Divyateja; Jignesh Bhate; Guruprasad K. S. Rao (Journal of Current Research in Scientific Medicine)
Neuropathic pain (NP) is defined as a process occurring after a primary lesion or disease of the somatosensory nervous system. The diagnosis of NP is a comprehensive process. The assessment begins with the medical history of the patient, conducting neurological assessments, and using pain scales to quantify pain intensity and measure sensory thresholds. NP treatment involves a diversity of pharmacological and nonpharmacological interventions, based on patient-specific characteristics, causal factors, medical history, and intensity of pain. Sociodemographic characteristics, psychological factors, and medical conditions are the potential predictors of the treatment response for an outcome. NP severely affects the quality of life of the patient. This review has reviewed the diagnostic approaches and management of NP through real-world evidence on the effectiveness of different lines of treatment.